Detecting two Schistosoma circulating antigens – CCA and CAA – in urine and serum to improve diagnosis of human schistosomiasis - Hoekstra, Pytsje T.; de Dood, Claudia J.; Abdoel, Theresia; Hilt, Stan; van Diepen, Angela; Polman, Katja; Kremsner, Peter; van Lieshout, Lisette; Kreidenweiss, Andrea; Adegnika, Ayola Akim; Fusco, Daniela; Rasomoelina, Tahinamandranto; et al. (Frontiers in Parasitology, 2024)
Background: Schistosomiasis is caused by infection with parasitic Schistosoma worms and affects more than 250 million people globally. The detection of schistosome derived circulating cathodic and anodic antigens (CCA and CAA) has proven highly valuable for detecting active Schistosoma infections, causing both intestinal and urinary schistosomiasis. Aim: The combined detection of CCA and CAA was explored to improve accuracy in detecting Schistosoma infections. Methods: Parallel detection of CCA and CAA was performed on two banked sample sets with matching serum and urine samples from Schistosoma mansoni (Sm) and S. haematobium (Sh) infected individuals using the non-concentration based lateral flow (LF) test comprising the sensitive luminescent up-converting reporter particle (UCP) technology. Results: Parallel detection of CCA and CAA increased the positivity rate for detecting both Sm and Sh infections compared to the detection of either antigen separately, demonstrating the added value of detecting both antigens in a single sample to confirm diagnosis, independent from the Schistosoma species. Significantly higher CCA concentrations in urine were observed in Sm infected individuals compared to Sh infected individuals, while serum CCA-concentrations were similar between species. CAA concentrations were higher in serum compared to those in urine, irrespective of species. When exploring the relationship of CCA and CAA in urine, the CCA/CAA ratio in Sm infected individuals was significantly higher than in Sh infected individuals, while no differences were observed in serum. Discussion & Conclusion: Parallel detection of CCA and CAA via the UCP-LF platform showed added diagnostic value through an increased positivity rate for the detection of Sm and Sh infections, compared to only detecting either of the antigens. The combined and quantitative detection of CCA and CAA is indicative for identifying the infecting species, but needs further exploration.